Behavior of domestic chickens – insights from a narrative review - Carvalho, Camila Lopes; Oliveira, Caroline Romeiro de; Galli, Gabriela Miotto; Camargo, Nathalia de Oliveira Telesca; Pereira, Melody Martins Cavalcante; Stefanello, Thais Bastos; Melchior, Raquel; Andretta, Ines (Revista de Ciências Agroveterinárias, 2022)
The intensification of poultry production systems has brought major changes in domestic fowls' physical and social environment. The management of these birds has received considerable attention in recent years due to new demands from consumers, especially those related to welfare. Behavior is the way that animals respond to the different stimuli they encounter in their environment. The behavioral expressions of poultry and the application of this knowledge in the care of the stock plays an important part in the maximization of the production efficiency of the poultry chain. Thus, defining ethical limits and guidelines for poultry production is essential to promote the development of new production practices, and by that ensure quality and productivity without putting bird welfare at risk. This review is based on scientific literature and highlights the main behavioral expressions of domestic chickens, including social, feeding, and reproductive expressions, in addition to stereotypes and strategies for social adaptation. Thus, it will promote to the reader and for the scientific community a better understanding about subjects that are not frequently discussed and by that help behavioral analyzes.